Sambucus nigra-Lyophilized Fruit Extract Attenuated Acute Redox–Homeostatic Imbalance via Mutagenic and Oxidative Stress Modulation in Mice Model on Gentamicin-Induced Nephrotoxicity - Kamelia Petkova-Parlapanska; Ivaylo Stefanov; Julian Ananiev; Tsvetelin Georgiev; Petya Hadzhibozheva; Veselina Petrova-Tacheva; Nikolay Kaloyanov; Ekaterina Georgieva; Galina Nikolova; Yanka Karamalakova (Pharmaceuticals)
Background: Gentamicin (GM) administration is associated with decreased metabolism, increased oxidative stress, and induction of nephrotoxicity. Sambucus nigra L., containing flavonoids, anthocyanins, and phytosterols, possesses antioxidant and anti-inflammatory potential. Objectives: The present study aimed to investigate the nephroprotective and anti-inflammatory potential of lyophilized Sambucus nigra fruit extract (S. nigra extract) to reduce acute oxidative stress and residual toxicity of GM in a 7-day experimental model in Balb/c rodents. Methods: The S. nigra extract was lyophilized (300 rpm; 10 min; −45 °C) to improve pharmacological properties. Balb/c mice were divided into four (n = 6) groups: controls; S. nigra extract per os (120 mg kg−1 day−1 bw); GM (200 mg kg−1 day−1 bw) (4); and GM + S. nigra therapy. The activities of antioxidant and renal enzymes, cytokines, and levels of oxidative stress biomarkers—Hydroxiproline, CysC, GST, KIM-1, PGC-1α, MDA, GSPx—were analyzed by ELISA tests. The ROS and RNS levels, as well as 5-MSL-protein oxidation, were measured by EPR spectroscopy. Results: The antioxidant-protective effect of S. nigra extract (120 mg kg−1) was demonstrated by reduced MDA, ROS, and RNS and increased activation of endogenous enzymes. Furthermore, S. nigra extract significantly reduced the expression of IL-1β, IL-6, IL-10, TNF-α, IFN-γ, and KIM-1 and regulated collagen/protein (PGC-1α and albumin) deposition in renal tissues. Conclusions: Histological evaluation confirmed that S. nigra (120 mg kg−1) attenuated renal dysfunction and structural damage by modulating oxidative stress and acute inflammation and could be used as an anti-fibrotic alternative in GM nephrotoxicity.